Impact of e-Velanmai (e-Agriculture): An ICT Enabled Extension Approach - Karthikeyan, C.; Mohanraj , K. (Indian Journal of Extension Education, 2014)
An impact assessment of the beneficiaries of 'e-Velanmai' was undertaken in Palar sub-basin district of Tamil Nadu. Palar  sub-basin consists of 3 Water user Associations (WUA). About 20 respondents were drawn randomly from each WUA making the total sample size to 60 beneficiaries of 'e-Velanmai' project. Partial budgeting technique was used to assess the  impact of e-Velanmai. The study compared conventional approach of extension with e-Velanmai approach on various  dimensions. The study also explored and presented the strengths, weaknesses, opportunities and challenges (SWOC) of  the ICT enabled extension model. Findings from the research showed that e-Velanmai has positively impacted farmers  and improved their income. The comparative analysis shows that e-Velanmai is comparatively effective method of  extension approach in various aspects.
Keywords: e-Velanmai; conventional extension; ICTbased extension; SWOC analysis